Political information sources for young citizens: a case study of Lithuanian youth information behavior - Šuminas, Andrius; Mierzecka, Anna (Information & Media, 2015)
The way young people obtain political information and engage with political content has changed since the new media technologies have emerged on a large scale. Starting with a discussion of different roles of online media in the transformation of political engagement, this article analyzes political engagement from the perspectives of political interest and participation in the context of new forms of online interaction. Findings from a national survey in Lithuania (n = 412, age 18 to 22) reveal the main sources and channels through which young people receive political information and news. The result of the study shows the importance of the Internet as a political information channel for the young people, however, the use of social media and other online channels for political engagement has been discovered to be low, especially with regard to two-way interactions with politicians or political parties.
Keywords: political information sources; media use; political information channels; political engagement; youth; information behavior